Comparison of one-stage treatment versus two-stage treatment for the management of patients with common bile duct stones: A meta-analysis - Nie, Shanmao; Fu, Shangyu; Fang, Kaiyan (Frontiers in Surgery, 2023)
Background: Cholelithiasis is a frequently occurring disease in clinic. Due to changes in people's living environments, dietary habits and the aging population, cholelithiasis incidence is increasing. Currently, laparoscopic cholecystectomy (LC) is the preferred treatment for gallbladder stones, but the surgical method for patients with choledocholithiasis is controversial. An endoscopic retrograde cholangiopancreatography (pERCP) is performed preoperatively, followed by LC as the general treatment method. However, pERCP still has some disadvantages, such as prolonged hospital stay, increased incidence of postoperative pancreatitis, and increased duration of anesthesia. Therefore, intraoperative endoscopic retrograde cholangiopancreatography (iERCP) is proposed. Objective: To compare the efficacy and safety of one-stage treatment and two-stage treatment for the management of patients with cholecystolithiasis and choledocholithiasis. Results: 9 RCTs (950 participants) were included in this meta-analyses. The overall morbidity rate in LC+iERCP group is lower than that in LC+pERCP group (RR: 0.57, 95% CI = 0.41–0.79, p = 0.0008). The clearance rate of choledocholithiasis in LC+iERCP group was almost the same as that in LC+pERCP group (RR: 1.03, 95% CI = 0.98–1.08, p = 0.28). The incidence of pancreatitis in LC+iERCP group is lower than that in LC+pERCP group (RR: 0.29, 95% CI = 0.13–0.67, p = 0.004). The length of operation of the LC+iERCP group seems to be similar to that of the LC+pERCP group (MD: 16.63 95% CI = -5.98–39.24, p = 0.15). LC+iERCP group has a shorter length of hospitalization than that in LC+pERCP group (MD: -2.68 95% CI = -3.39–-1.96, p < 0.00001). LC+iERCP group has lower postoperative second ERCP rate than that in LC+pERCP group (RR: 0.13, 95% CI = 0.03–0.57, p = 0.006). Conclusion: Our study suggest that LC+iERCP may be a better option than LC+pERCP in the management of patients with both cholecystolithiasis and choledocholithiasis. This procedure can reduce the overall incidence of postoperative complications, especially the occurrence of postoperative pancreatitis. It could shorten the length of hospital stay, reduce postoperative second ERCP rate.